2014
DOI: 10.1093/rheumatology/keu421
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog signalling pathway regulates apoptosis through Smo protein in human umbilical vein endothelial cells

Abstract: The Shh signalling pathway plays a role in regulating endothelial cell apoptosis in a Smo-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Although most of the studies focused on the role of Hh signaling in the morphogenesis, this pathway is multifaceted and regulates a broad spectrum of other processes including tissue maturation, cell fate decisions (proliferation, apoptosis, migration, and differentiation), and maintenance of stem cell population [ 16 , 17 , 18 , 19 , 20 ]. In line with this notion, activation of the Hh signaling is not only a typical feature of embryogenesis, but it has been also observed in the postnatal period, where it maintains tissue homeostasis and drives repair and regeneration following injury [ 21 , 22 , 23 ].…”
Section: Hedgehog Signaling In Cancermentioning
confidence: 99%
“…Although most of the studies focused on the role of Hh signaling in the morphogenesis, this pathway is multifaceted and regulates a broad spectrum of other processes including tissue maturation, cell fate decisions (proliferation, apoptosis, migration, and differentiation), and maintenance of stem cell population [ 16 , 17 , 18 , 19 , 20 ]. In line with this notion, activation of the Hh signaling is not only a typical feature of embryogenesis, but it has been also observed in the postnatal period, where it maintains tissue homeostasis and drives repair and regeneration following injury [ 21 , 22 , 23 ].…”
Section: Hedgehog Signaling In Cancermentioning
confidence: 99%
“…Asai et al have shown that SHH directly promotes the migration, adhesion, proliferation and even tube formation of endothelial progenitor cells [42]. Other studies have indicated that SHH application protects against apoptosis in endothelial cells, while the SMO-specific inhibitor enhances TNF-a-induced apoptosis in HUVECs [43,44]. Regarding Hedgehog-Gli1 signaling activation in HUVECs induced by the MNTs, we paid further attention to Hedgehog-Gli1 signaling and investigated its potential roles in mediating biological effects of the biomaterial topographies.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that cyclopamine significantly suppressed the gene and protein expression of Smo and Gli1 nuclear accumulation, which was consistent with previous studies. 50,51 Treatment with cyclopamine decreased the proliferative activity of MG63 cells, especially the cells seeded onto MNTs. Furthermore, the enhanced expressions of the osteogenesis-related genes (BMP-2, ALP, and Runx2) and ALP production enabled by the MNTs were significantly downregulated by the presence of cyclopamine to a similar level as those on the smooth and acid-etched microstructured surfaces in the absence of cyclopamine.…”
Section: Discussionmentioning
confidence: 99%